Analysis of the physical preparation of the Ecuadorian champion of pole vault Dyander Pacho in 2020/2021 - Guadamud, Luis Lucas; Aguilar Morocho, Elva Katherine (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of the present study was to analyze the physical preparation of the Ecuadorian champion of pole vault Dyander Pacho in 2020/2021. We applied analytical-descriptive statistical methods of a quantitative nature, analyzing the exercises applied in the 2020 and 2021 planning. Better results were found in the year 2021 (48.08) than in the year 2020 (43.76), although this difference was not statistically significant (p = 0.167). These results allowed us to conclude that the physical work program by itself does not significantly improve the pole vault, making necessary to carry out a complete work for the athlete.